confronting adultcentrism: childist and decolonial interventions in educational philosophies and institutions - biswas, tanu; rollo, toby (childhood & philosophy, 2024)
'Confronting Adultcentrism: Childist and Decolonial Interventions in Educational Philosophies and Institutions' explores the transformative potential of childism as an orientation to critique and transform adultism and coloniality within education. Edited by Tanu Biswas and Toby Rollo, the special dossier builds on the Childism Institute’s discussions to center children as epistemic agents and challenge the structural marginalization of childhood in socio-political and philosophical spheres. Childism deconstructs and critiques adult-centric biases, proposing a profound shift toward recognizing the interdependence of childhood and adulthood, and unique relational perspectives as vital to intergenerational justice. The articles examine how traditional (euro-centric) educational systems reinforce adultist hierarchies, viewing children as incomplete beings in a preparatory phase called 'childhood'. They advocate for reimagining educational systems with age-inclusive pedagogical relationships where children participate as active contributors. Key themes include democratic education and liberation as an intergenerational project,, decolonial critiques of childhood philosophies underlying educational practices, and the role of children as epistemic agents and activists. Some contributions argue for dismantling adultist structures and integrating children and childhood into democratic and liberatory frameworks. Others explicitly link adultism to coloniality, showing how Eurocentric colonial projects infantilized colonized peoples. The articles extend childism’s reach to address historical legacies of racialized and epistemic oppression including explorations of racialized imageries of childhood. Collectively the dossier advances childism as a timely intervention for reshaping education, philosophy, and policy, embracing children’s present contributions and fostering intergenerational equity.